ADAMTS-5 Decreases in Aortas and Plasma From Aortic Dissection Patients and Alleviates Angiotensin II-Induced Smooth Muscle-Cell Apoptosis - Zeng, Tao; Gan, Jianting; Liu, Yu; Shi, Lei; Lu, Zhengde; Xue, Yan; Xiong, Rixin; Liu, Ling; Yang, Zicong; Lin, Yingzhong; Yuan, Jun (Frontiers in Cardiovascular Medicine, 2020)
Background: Acute aortic dissection (AAD) is associated with degeneration of the aortic media and accompanied by vascular extracellular matrix (ECM) remodeling. Recently, a disintegrin and metalloproteinase with thrombospondin type 1 motifs-5 (ADAMTS-5) has been reported to be involved in ECM remodeling and vascular diseases. The aim of this study was to examine ADAMTS-5 levels in AAD patients and investigate the underlying mechanisms. Methods: Aortic tissue samples were collected from normal donors and AAD patients, and the expression of ADAMTS-5 was analyzed in all aortic tissues. In addition, plasma levels of ADAMTS-5, matrix metalloproteinase (MMP)-2 and MMP- 9 and tumor necrosis factor-α (TNF-α) were measured in repeated samples from AAD patients and compared to the non-AAD (NAD) group. In addition, we investigated the effects of ADAMTS-5 in smooth muscle cell (SMC) apoptosis. Results: The results showed that ADAMTS-5 expression was significantly reduced in the aortas of AAD patients and that SMCs were the main source of ADAMTS-5. In addition, the plasma ADAMTS-5 level was lower, but plasma MMP-2, MMP-9 and TNF-α levels were increased in the AAD patients. Multivariate linear regression analyses showed that a decreased ADAMTS-5 level in patients was independently associated with an increased risk of AAD. Furthermore, recombinant human ADAMTS-5 significantly ameliorated angiotensin (Ang II)-evoked SMC apoptosis. Conclusions: ADAMTS-5 shows promise as a novel potential biomarker for AAD, and regulation of SMC is a possible mechanism for the effects of ADAMTS-5.